2018
DOI: 10.1007/s41548-018-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism rs17849071 G/T in the PIK3CA gene is inversely associated with oral cancer

Abstract: Purpose Oral squamous cell carcinoma (OSCC)-a subset ofhead and neck cancer is the sixth most common cancer worldwide and leading disease in India. The genes involved in PI3 K/AKT (Phosphatidylinositol 3-kinase-Akt) pathway, such as PIK3CA (Phosphoinositide-3-kinase catalytic α) and PTEN (Phosphatase and tensin homologue) were found to be associated with OSCC. The present study was aimed to find the genetic association of various polymorphisms in intron 9 of the PIK3CA gene and intron 5 of PTEN gene with prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Highly frequent mutations in this gene were first reported by Samuel et al [ 35 ], which vary from 0% to 21% [ 36 , 37 ]. A study from India found polymorphism rs17849071 G/T in this gene to be inversely linked to OC [ 38 ]. A significant correlation between somatic mutations and disease stage was also reported [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Highly frequent mutations in this gene were first reported by Samuel et al [ 35 ], which vary from 0% to 21% [ 36 , 37 ]. A study from India found polymorphism rs17849071 G/T in this gene to be inversely linked to OC [ 38 ]. A significant correlation between somatic mutations and disease stage was also reported [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HPV screening must require before any genetic analysis of the cancer patient. This is the personalized medicine era, based on the patient's genomic pro le; the prognosis of the patients can be improved [70]. The patients with HPV infection has better prognosis than any other personal history.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to betel quid and tobacco carcinogens can result in the commencement of oral cancer. The exposure to carcinogens released by tobacco smoke and betel quid chewing for a long time results in augmenting chronic inflammatory reactions in oral tissues, which consequently leads to genetic alterations and finally causes oral carcinogenesis [7][8][9]. Keeping this in mind, we checked the collective impact of RETN SNPs and these environmental carcinogens.…”
Section: Retn Haplotype Association With Oscc Susceptibilitymentioning
confidence: 99%
“…SNP studies on diverse populations emphasize the association of these genetic variants with the predisposition and vulnerability to Oral Squamous Cell Carcinoma (OSCC) [6,7]. For example, the genes involved in PI3K/AKT pathway [9], IL-8 [8], miR [1] genes, TNF-α etc., are found to be associated with Oral Squamous Cell Carcinoma (OSCC). These studies have proved that the identification of gene variants can be an important aspect for the early-stage diagnosis of Oral Squamous Cell Carcinoma (OSCC).…”
Section: Introductionmentioning
confidence: 99%